“I am Rwandan”: unity and reconciliation in post-genocide Rwanda - Blackie, Laura E.R.; Hitchcott, Nicki (International Association of Genocide Scholars, 2018)
Drawing on a corpus of ten oral interviews with survivors and perpetrators of the 1994 Genocide against the Tutsi in Rwanda, we examine how the government’s policy of unity and reconciliation has shaped post-genocide identities and intergroup relations in local Rwandan communities. By focusing on the relationships between individuals and the national post-genocide narrative, we show how the socio-political context in Rwanda influences how people locate themselves and how they ascribe rights and duties to and in relation to others. Specifically, we use positioning theory as an interpretive lens to argue that individuals view adherence to the government’s post-genocide narrative of unity and reconciliation as a moral duty, which is vital to continued political stability and economic development in Rwanda. Our discussion focuses on explaining how the social positioning of the national post-genocide narrative may function to reinforce the ethnic tensions the government has pledged to eradicate.